Age variation in patients with troponin level elevation without obstructive culprit lesion or suspected myocardial infarction with non-obstructive Coronary arteries: long-term data covering over decade - Abumayyaleh, Mohammad S. A.; Schlettert, Clara; Materzok, Daniel; Mügge, Andreas; Hamdani, Nazha; Akın, Ibrahim; Aweimer, Assem; El-Battrawy, Ibrahim (Journal of Clinical Medicine, 2024)
Background/Objectives: Troponin level elevation without an obstructive culprit lesion is caused by heterogenous entities. The effect of aging on this condition has been poorly investigated. Methods: After screening 24,775 patients between 2010 and 2021, this study included a total of 373 patients with elevated troponin levels without an obstructive culprit lesion or suspected myocardial infarction with non-obstructive coronary arteries (MINOCAs) categorized into four age groups containing 78 patients (<51 years), 72 patients (51-60 years), 81 patients (61-70 years), and 142 patients (>70 years). This study analyzed the baseline characteristics, the in-hospital complications, in-hospital mortality, and the long-term outcomes. Results: The older patients exhibited a higher rate of major adverse cardiovascular in-hospital events than those of the other age groups (15.4% in the <51-year-old group vs. 36.1% in the 51-60-year-old group vs. 33.3% in the 61-70-year-old group vs. 47.2% in the >70-year-old group; p < 0.001). However, the rate of non-sustained ventricular tachycardia (nsVT) was higher in the 51-60-year-old patients than those of the other age groups (5.6% in the 51-60-year-old group vs. 1.3% in the 61-70-year-old group vs. 0.7% in the >70-year-old group; p = 0.027). At the 11-year follow-up, cardiovascular mortality was higher among the older patients compared to that of the younger patients (3.9% in the 61-70-year-old group vs. 4.2% in the >70-year-old group, p = 0.042), while non-cardiovascular mortality was comparable between the age groups. Conclusions: The older patients with troponin level elevation without an obstructive culprit lesion experienced a higher incidence of major adverse cardiovascular events during hospitalization compared to that of the younger groups. Additionally, higher cardiovascular mortality rates were revealed in the older patients at a long-term follow-up.
Gesehen am 03.04.2025